KORELASI ANTARA KADAR HEMOGLOBIN A1C DENGAN ESTIMATED GLOMERULAR FILTRATION RATE PADA DEWASA - Bisma Narendra Tama; Ronald Irwanto Natadidjaja (Jurnal Akta Trimedika, 2026)
Glycated hemoglobin has been considered an indicator of long-term glycemic control that may be associated with renal function; however, previous studies investigating its relationship with estimated glomerular filtration rate in adult populations have reported inconsistent findings. This study aimed to analyze the correlation between glycated hemoglobin levels and estimated glomerular filtration rate in adults. An observational analytic study with a cross-sectional design was conducted at Soehadi Prijonegoro Regional General Hospital from October to November 2025. A total of 56 adult subjects aged over 18 years who met the inclusion and exclusion criteria were analyzed using secondary data obtained from medical records. Glycated hemoglobin levels and serum creatinine were collected to calculate estimated glomerular filtration rate using the 2021 Chronic Kidney Disease Epidemiology Collaboration equation without a race component. Correlation analysis was performed using the Spearman test with a significance level of less than 0.05. The study subjects consisted of 29 males and 27 females with a median age of 53 years. The median glycated hemoglobin level was higher in females than in males, while the median estimated glomerular filtration rate was slightly higher in males than in females. Spearman correlation analysis showed a very weak negative correlation that was not statistically significant between glycated hemoglobin and estimated glomerular filtration rate. This study concludes that there is no significant association between glycated hemoglobin levels and renal function in adults with relatively normal kidney function.